Effect of Workload and Competence on Employee Performance Mediated by Work Stress Among Employees of PT Andalan Artha Primanusa (Jurnal Bisnis dan Manajemen West Science, 2026)
This study aims to analyze and prove the effect of workload and competence on employee performance, with work stress as a mediating variable among employees of the Plant Department at PT Andalan Artha Primanusa. The background of this research is based on the decline in the achievement of Key Performance Indicators (KPI) for the heavy-equipment maintenance function during the 2024–2025 period. This research uses a quantitative approach with an explanatory design. The sample consisted of 100 respondents selected using a purposive sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that workload has a significant negative effect on employee performance and a significant positive effect on work stress. Competence has a significant positive effect on employee performance and a significant negative effect on work stress. Work stress has a significant negative effect on employee performance. Mediation testing confirms that work stress significantly mediates the effect of both workload and competence on employee performance. These findings support the Job Demands-Resources (JD-R) Theory, in which the balance between job demands and job resources strongly influences employee stress levels and performance. The company is advised to evaluate workload targets, regularly improve technical knowledge, and manage occupational health to minimize stress and increase productivity.
Keywords: Workload; Competence; Work Stress; Employee Performance; PLS-SEM